Peran Pemerintah Desa Dalam Memberdayakan Masyarakat Melalui Olahan Susu Sapi Di Desa Pinang Kecamatan Cendana Kabupaten Enrekang - Mardhan Alqadri; Sakaruddin Mandjarreki; Hamriani; Sattu Alang (Jurnal Berita Sosial, 2025)
This study aims to determine how the village government's efforts in community empowerment through cow's milk processing in Pinang village, Cendana sub-district, Enrekang district. The main focus of the research is the efforts made by the Pinang Village Government and the impact (results) of the community empowerment program through cow's milk processing. This research will explore how the strategy and implementation of the village program contribute to improving the knowledge, skills, and economic and social welfare of the community. This research uses a qualitative approach with observation, interview, and documentation. The Pinang Village Government empowers the community through cow's milk processing with seminars, training, and ongoing mentoring, supported by infrastructure and equipment assistance. This effort aims to increase the community's knowledge and skills in producing cow's milk to the maximum and marketing it. As a result, the program succeeded in improving the community's economy, creating new sources of income, and encouraging business sustainability and food security.